2013
DOI: 10.1590/0074-0276108062013008
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity expressed by Shigella sonnei: identification of a putative new bacteriocin

Abstract: Bacteriocins are antibacterial, proteinaceous substances that mediate microbial dynamics. Bacteriocin production is a highly disseminated property among all major lineages of bacteria, including Shigella. In this paper, we addressed the purification and characterisation of a bacteriocin produced by a Shigella sonnei strain (SS9) isolated from a child with acute diarrhoea. The substance was purified through ammonium-sulphate precipitation and sequential steps of chromatography. The intracellular fraction obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…According to the results, bacteriocin SF1 maintains antibacterial capacity at 80°C, but not at 100°C. The thermolability at 100 and 121°C of this antagonistic substance is also consistent with its chemical composition and corroborates data reported by other authors who have demonstrated that colicins produced by Shigella are generally heat labile [7, 20]. By SDS-PAGE, a single band was obtained for bacteriocin SF1.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results, bacteriocin SF1 maintains antibacterial capacity at 80°C, but not at 100°C. The thermolability at 100 and 121°C of this antagonistic substance is also consistent with its chemical composition and corroborates data reported by other authors who have demonstrated that colicins produced by Shigella are generally heat labile [7, 20]. By SDS-PAGE, a single band was obtained for bacteriocin SF1.…”
Section: Discussionsupporting
confidence: 90%
“…Enzyme solutions were filter-sterilized (Millex-GP, 0.22 µm, PES), aliquots of C-50 and C-80 were two-fold diluted in each enzyme solution, and mixtures were incubated at 37ºC for 2 h. Remaining antagonistic activity after enzyme treatment was determined as described previously. Diluted C-50 and C-80 (0.01 M Tris-HCl, pH 7.2) and enzyme solutions were used as controls [28].…”
Section: Effect Of Physicochemical Factors On Antagonistic Activitymentioning
confidence: 99%
“…After centrifugation at 29,830 g, for 30 min, at 4° C sediments were dissolved in the same buffer, generating the intracellular extracts named as C-30 and C-75. C-75 was dialyzed against the same buffer at 4°C overnight, aliquoted, and kept at -80 °C (Moreira, 2011, Sousa et al 2013.…”
Section: Intracellular Protein Extractionmentioning
confidence: 99%
“…After incubation at the same conditions described before, the presence of inhibition zones was considered indicative of antagonistic activity. Tris-HCl buffer and ultrapure water were employed as controls (Booth et al 1977;Sousa et al 2013). The assay was used to determine the antagonistic activity of the samples obtained from the purification steps.…”
Section: Evaluation Of Antagonism Expression Titration and Determinat...mentioning
confidence: 99%